Pengaruh Kualitas Sistem Kualitas Layanan dan Pemasaran Relasional terhadap Loyalitas Pengguna BSB Mobile pada Bank Sumsel Babel Syariah Palembang dengan Kepuasan Pengguna sebagai Variabel Intervening - Lestari, Winda Fuji; Isnurhadi, Isnurhadi; Maulana, Ahmad (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aimed to analyze the factors influencing user satisfaction and loyalty in using the BSB Mobile application at the Bank Sumsel Babel Palembang Syariah Branch. This research focuses on system quality, service quality, and relational marketing as variables that potentially enhance user satisfaction and loyalty. Research methodology: A quantitative approach was employed using PLS-SEM for data analysis with SmartPLS. The study sample consisted of 266 purposively selected mobile BSB users. Data were collected through an online questionnaire. Descriptive demographic analysis was conducted using SPSS to determine the respondent characteristics. Results: The results indicate that system quality, service quality, and relational marketing have positive and significant effects on user satisfaction. User satisfaction acts as a mediator, enhancing the influence of these factors on user loyalty. These findings demonstrate the critical role of system quality, service quality, and relational marketing in fostering user loyalty to BSB Mobile apps. Limitations: This study focuses only on system quality, service quality, and relationship marketing on user loyalty with user satisfaction as intervening variables in the Syariah Palembang Branch. Contribution: This study is expected to provide deeper insight into the  effects of system quality, service quality, relationship marketing to user loyalty with user satisfaction as an intervening variable.